Profil Proses Berpikir Siswa dalam Mengolah Informasi Yang Ditayangkan Media Pembelajaran Fisika: Slide Presentasi - Desi Yuliana Rudjubik; Alvama Pattiserlihun; Wahyu Hari Kristiyanto (JURNAL PEMBELAJARAN FISIKA, 2019)
Abstract Given the importance of train students to turn think cognitive and thinking criticial in cultivate the information the have learning media who used to assist student in processes information through slideshow presentation. The purpose of this research is described though process profile students in processes information posted learning of media physics slide presentation. The methodology used is the the methodology naturalistic qualitative, where researchers acting as an instrument major obtain information from the subject of study sub focus on research conducted on natural conditions (Natural Setting), it is neither condition. This research result indicates that thought proces profile students in processes information posted media learning physics slide presentation can produce thought process in assimilation students and accommodation. This research it can be concluded that slide presentation is not effective because in the use of slide presentation has to be in accordance with matter physics, the implications of these procesess misconception remedation physics research is still difficult done if had a slide presentation because the thought process in acommodation in this research would look like if the experiments that were put into slide presentation. Key word: the thinking process, learning media, slide presentation, learning physics